Climate Investment Partnership Roundtable - Chevallier, Romy; Trautman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The African Union Commission (AUC) hosted the Strategic Climate Investment Partnership roundtable from 19-20 June 2023 at the African Union (AU) Headquarters in Addis Ababa, Ethiopia. This roundtable, attended by key development partners, financial organisations, technical bodies, the private sector, and other institutions, was organised to leverage partnerships and align investment opportunities to support the operationalisation of the African Union Climate Change and Resilient Development Strategy and Action Plan (2022-2032).